The Kajeng Kliwon Ritual and Its Relevance in The Modern Era - Wayan Gama, I (Advances In Social Humanities Research, 2025)
This article examines the holy day of Hinduism in Bali, namely 'Kajeng Kliwon'. This holy day includes Bhuta Yadnya. According to the Balinese Calendar, this sacred day appears once every fifteen days, precisely during the meeting; A trio of squirrels and squirrels. This sacred day is believed to be very magical, as a dark time, (a moment of supernatural power or negative energy, disturbing the tranquility of human life). The focus of the study on what animates Kajang Kliwon is such a magical day. Why are the Hindu community in Bali so confident that the offerings of segehan can build a harmonious universe. How does this ritual face the challenges of modernization, dedigitization and the demands of the harmonization of life in the future? The method used is a literature review with a qualitative approach, namely studying Hindu literature texts, as well as modern research on spiritual, philosophical and socio-cultural values. The results of the study show that the Kajang Kliwon ritual revealed; sacrifice, spirituality, self-purification, and intimacy, so that they remain relevant as moral, social, and spiritual guidelines in the contemporary era. At the same time, it strengthens the harmony between humans, nature, and spirituality.